“Green structures” as a tool for reducing the environmental risks of urban ecosystems - Tkachenko, T.; Voloshkina, O. (My University, 2019)
Modern urbocenosis is an unstable artificial ecosystem. Under the influence of natural and man-made factors, urbocenoses are subject of environmental, economic and social risks. Optimal using and restoration of natural areas is one of the ways to reduce the risks of urbocenoses, a way to increase their stability and sustainable development.
Keywords: Green structures; urban ecosystem; environmental risk